COVID-19 AND EDUCATION MANAGEMENT: THE CASE OF SILESIAN REGION - POLAND (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
COVID-19 outbreak has changed the economic and social relations and caused a critical impact on the higher education system. The closure of University campuses to prevent community transmission of the Coronavirus SARS-CoV-2 has shifted face-to-face classes to online learning, distance learning, e-learning, mobile learning, and social learning. E-Learning and virtual education may become an essential component of the higher education system in the next years. Accordingly, teaching staff had to adapt their teaching methodology and tools to eLearning tools and platforms for effective student engagement. This paper reports on a first study conducted from December 2020 to January 2021, involving one hundred Higher Schools teachers of Management in the Silesia Region.The study showed many serious problems related to the emergency teaching-learning experience since it was essentially based on the translation of face-to-face approach in the online environment.